Effective synthesis of quinoxalines over ceria based solid acids coated on honeycomb monoliths - Venkatesh, -; Shamshuddin, S.Z.M.; Mubarak, N.M. (Scientific Publishers, 2015)
Solid acids of ceria such as sulfated ceria, ceria-zirconia mixed oxide and sulfated ceria-zirconia have been coated on honeycomb monoliths by slurry coating method. The catalyst materials are characterized by NH3-TPD for surface acidity, powder XRD for crystallinity and SEM for morphology. These materials are used as solid acid catalysts in the condensation reaction of various diamines and diketones to synthesize quinoxalines. In order to optimize the reaction conditions, the effect of reaction parameters such as the catalyst type, nature of the solvent, reaction temperature, nature of the catalyst and number of reaction cycles on the yield of the quinoxaline product has been studied. A correlation between the surface acidity and the catalytic activity is observed. The catalyst materials have also been prepared in their powder forms by impregnation method and their catalytic activity is compared with that of their honeycomb coated forms. The ceria based solid acids coated on honeycomb monoliths are economical, efficient and eco-friendly in quinoxaline synthesis.